Altered flow and sediment transport impacts on the ecosystems of Chinese major rivers: An urgent call for eco‐fluvial dynamics - Hongwei Fang; Guojian He; Lei Huang; Chenwei Zhao; Jianyu Wang; Yong Han; Qifeng Gao; Tao Zhang; Jianan Meng (River)
Abstract River ecosystems face challenges due to environmental degradation and alterations in flow and sediment transport resulting from climate change and other anthropogenic impacts. These changes may substantially affect river morphology, nutrient dynamics, wetland vegetation, aquatic habitats, and river ecological stability. This highlights the urgent need for systematic and quantitative studies on the interactions and feedback between changes in flow, sediment transport, and river ecology. In this study, we reviewed flow and sediment transport changes in major Chinese rivers, along with their resulting ecological impacts. We propose conducting eco‐fluvial dynamic studies, a potential solution that can guide the evaluation and restoration of ecological health impacted by physical processes. These studies can provide major benefits in balancing human and environmental needs in large river systems, which is crucial for the healthy and sustainable development of rivers.